Geotechnical engineering state of the art and practice : keynote lectures from GeoCongress 2012 - GeoCongress 2012 (2012 : Oakland, Calif.); Rollins, Kyle M.; Zekkos, Dimitrios; American Society of Civil Engineers. Geo-Institute. (Reston, Va. : American Society of Civil Engineers, 2012)
Includes bibliographical references and indexes.